Unlocking the Potential of Photoelectrochemical Water Splitting via Heterointerface Charge Polarization - Li Xu; Xingming Ning; Jingjing Quan; Chenglong Li; Lan Yao; Qiang Weng; Pei Chen; Zhongwei An; Xinbing Chen (Advanced Science, 2025)
Abstract The coupling of semiconductor (SC) and transition metal oxyhydroxide (TMOOH) is a promising approach for solar fuel production. However, the inevitable interfacial charge recombination and sluggish oxygen evolution reactions severely hinder the application of photoelectrochemical (PEC) device. This study demonstrates an innovative charge polarization strategy that simultaneously enhances both long‐range charge transfer and surface catalytic reaction dynamics through the rational construction of CoOx/MnOx heterointerface in SC/TMOOH system. Kelvin probe force microscopy, in situ ultraviolet/visible spectroelectrochemistry, and density functional theory calculations indicate that the tunable charge polarization of Coδ− and Mnδ+ can affect influences the SC/TMOOH and TMOOH/electrolyte interfaces, primarily through inducing the accelerated charge transfer dynamics (Kh) and diminishing the adsorption of oxygen‐containing intermediates. As anticipated, the BiVO4/CoOx/MnOx/FeNiOOH exhibits an impressive photocurrent of 6.75 mA cm−2 at 1.23 VRHE, along with a superior photostability. Furthermore, the smart approach can also be harnessed in the BiVO4/CoOx/CeOx/FeNiOOH photoanode. This study provides a novel polarization strategy for the design of optimal photoanodes for PEC water splitting.